The Relationship between Library Facilities and Library Services with Reading Interest of Class IV Students - Safitri, Ayu; Widagdo, Arif (Universitas Negeri Semarang, 2020)
This research aims to study the correlation between library facilities, library service and Grade IV Elementary School students reading interest. This study uses correlative type of research. The sample is taken from students grade IV in elementary school, Gugus Cakra, Ngaliyan sub-district, Semarang City with Simple Random Sampling technique. The data is collected using polls, interviews, observations, and documentation. The data is analyzed using some techniques including prerequisite tests for analysis and final data analysis. The result shows that the correlation between library facilities and reading interest acquired Rvalue 0.628. The correlation between service libraries and reading interest acquired Rvalue 0.625. Relation of library facilities and service libraries with the interest of reading students obtained a value of 0.716.